Capturing composites manufacturing waste flows through process mapping. (15th March 2015) - Rybicka, Justyna; Tiwari, Ashutosh; Alvarez Del Campo, Pedro; Howarth, Jack
Abstract: The necessity of high performance materials has become latent in high technology sectors such as aerospace, automotive, renewable energy, nuclear engineering and sports. The expanding impact on future manufacturing of the EU waste management legislation and increasing price of current waste management methods stress the importance of an efficient and sustainable way of recycling waste generated in the composites industry. Aerospace companies estimated that 30–50% of materials in aircraft production are scrapped due to the way it is manufactured. Companies need to pay for landfilling the composite materials that otherwise can be a valuable resource. In a view that looking at individual production waste outputs could maximise the material reuse or recycling capability, gaining information about the type of scrap materials could inform the development of composite reuse/recycling supply chain. This research paper focuses on understanding the scale of scrap created in individual composites manufacturing processes to assess its potential value in terms of reuse/recycle capabilities. A Material flow analysis based data collection workshop has been performed with four composite manufacturers. Through the case studies it has been identified that there are three fibre related waste outputs captured: dry fibres, fibre material sheet off-cuts, and curried composite off-cuts. The captured information allows for the material specification development. This allows bridging the gap between the manufacturers and the waste processors in composites to address the lack of infrastructure and lack of waste material specification barriers outlined by the Composites Strategy 2009. Highlights: Material Flow Analysis based method has been developed to capture composites manufacturing waste. Individual production material efficiency realisation. Capturing material specification to allow assessment for suitable recycling technologies.